Design and management considerations for control groups in hybrid effectiveness-implementation trials: Narrative review & case studies - Jurczuk, Magdalena; Thakar, Ranee; Carroll, Fran E.; Phillips, Lizzie; Meulen, Jan van der; Gurol-Urganci, Ipek; Sevdalis, Nick (Frontiers in Health Services, 2023)
Hybrid effectiveness-implementation studies allow researchers to combine study of a clinical intervention’s effectiveness with study of its implementation with the aim of accelerating the translation of evidence into practice. However, there currently exists limited guidance on how to design and manage such hybrid studies. This is particularly true for studies that include a comparison/control arm that, by design, receives less implementation support than the intervention arm. Lack of such guidance can present a challenge for researchers both in setting up but also in effectively managing participating sites in such trials. This paper uses a narrative review of the literature (Phase 1 of the research) and comparative case study of three studies (Phase 2 of the research) to identify common themes related to study design and management. Based on these, we comment and reflect on: (1) the balance that needs to be struck between fidelity to the study design and tailoring to emerging requests from participating sites as part of the research process, and (2) the modifications to the implementation strategies being evaluated. Hybrid trial teams should carefully consider the impact of design selection, trial management decisions, and any modifications to implementation processes and/or support on the delivery of a controlled evaluation. The rationale for these choices should be systematically reported to fill the gap in the literature.